2019
DOI: 10.1002/ar.24246
|View full text |Cite
|
Sign up to set email alerts
|

You Can't Run, but You Can Hide: The Skeleton of the Sand‐Swimmer LizardCalyptommatus leiolepis(Squamata: Gymnophthalmidae)

Abstract: Squamates exhibit a vast diversity of body plans, which directly determines habitat use and preference. Here the skeleton of the sand-swimmer burrower gymnophthalmid, Calyptommatus leiolepis, is analyzed to investigate how its peculiar fossorial locomotion affects its osteology. Calyptommatus leiolepis is a limb-reduced, short-intermediate tailed lizard. Although there are other studies on its general anatomy, we performed a detailed description of its skeleton. Using high-resolution computer tomography, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Lizards occupy a wide diversity of habitats (e.g., terrestrial, arboreal, saxicolous, fossorial, sand dwellers, semi-aquatic, and aquatic), and for this reason, it is expected that they exhibit significant variation in their middle ear structure depending on the way and medium through which they perceive sounds. As anticipated, according to the literature, the columella bone is a constant element with an uniaxial organization, although differs in shape and proportions (ranging from being long and thin as in Tupinambis nigropunctatus = Tupinambis teguixin ( Jollie, 1960 ) to short and stumpy as in Calyptommatus leiolepis ( Holovacs et al, 2020 )). The extracolumella on the other hand, shows more significant variation in the number and shape of its processes ( Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Lizards occupy a wide diversity of habitats (e.g., terrestrial, arboreal, saxicolous, fossorial, sand dwellers, semi-aquatic, and aquatic), and for this reason, it is expected that they exhibit significant variation in their middle ear structure depending on the way and medium through which they perceive sounds. As anticipated, according to the literature, the columella bone is a constant element with an uniaxial organization, although differs in shape and proportions (ranging from being long and thin as in Tupinambis nigropunctatus = Tupinambis teguixin ( Jollie, 1960 ) to short and stumpy as in Calyptommatus leiolepis ( Holovacs et al, 2020 )). The extracolumella on the other hand, shows more significant variation in the number and shape of its processes ( Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Segmentation of individual ossicles was challenging, as they were rarely distinct. This may be an artifact of the scan or may indicate a high level of fusion, as seen in other burrowers [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Basicranial sesamoids are found in many squamate families, including Scincidae, although previous examination of an acontine did not find any [ 6 , 71 ]. They are typically small in non-fossorial squamates, but can be large in burrowers to provide a larger attachment site for the longus colli muscle [ 53 , 71 ]. A larger longus colli muscle, which pulls the head down, may allow for the generation of greater forces for burrowing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other aspects of head shape may also affect burying performance. For example, the sandfish skink (Scincus scincus) and South American gymnophthalmid species that burrow in looser soil have pointy, shovel-like snouts [42,70,71]. We tested this idea and found that more snake-like species had more gently sloping snouts (electronic supplementary material, figure S2C), but that pointiness was unrelated to body form (electronic supplementary material.…”
Section: (B) Locomotion and The Re-evolution Of Quadrupedal Formmentioning
confidence: 99%